2008
DOI: 10.1007/s00428-007-0557-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic aberrations of ovarian and uterine carcinosarcomas—a CGH and FISH study

Abstract: The origin of carcinosarcomas of the ovary and uterus has long been discussed. In this study, we used a molecular-genetic approach to elucidate the tumorigenesis of carcinosarcomas of these organs correlating our findings with the specific biphasic pattern of these tumors. We analyzed a series of 30 paraffin-embedded carcinosarcomas of the ovary and the uterus using comparative genomic hybridization (CGH) and fluorescence in-situ hybridization (FISH). In general, gains (85%) were observed more frequently, than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 36 publications
1
45
0
1
Order By: Relevance
“…We did not observe this gain frequently in endometrioid tumors, but it was a recurrent aberration (56%) in the nonendometrioid tumors. Schipf et al (2008) and Schulten et al (2004) also described a frequent gain of 8q in the majority of carcinosarcomas. Furthermore, the frequent gain of 20q (60% of our samples) is in line with the 75% gain in nonendometrioid tumors reported by Schipf et al However, many additional losses were found in our study (Supporting Information Table S2), which were not described by Schipf et al (2008).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We did not observe this gain frequently in endometrioid tumors, but it was a recurrent aberration (56%) in the nonendometrioid tumors. Schipf et al (2008) and Schulten et al (2004) also described a frequent gain of 8q in the majority of carcinosarcomas. Furthermore, the frequent gain of 20q (60% of our samples) is in line with the 75% gain in nonendometrioid tumors reported by Schipf et al However, many additional losses were found in our study (Supporting Information Table S2), which were not described by Schipf et al (2008).…”
Section: Discussionmentioning
confidence: 91%
“…Schipf et al (2008) and Schulten et al (2004) also described a frequent gain of 8q in the majority of carcinosarcomas. Furthermore, the frequent gain of 20q (60% of our samples) is in line with the 75% gain in nonendometrioid tumors reported by Schipf et al However, many additional losses were found in our study (Supporting Information Table S2), which were not described by Schipf et al (2008). This may have technical reasons, like platform use, or may be due to the samples selection (tumor grade, number of tumors studied).…”
Section: Discussionmentioning
confidence: 91%
“…Carcinosarcoma metastases to other organs most commonly derive from the carcinomatous pattern [3,4,15,18]. It is difficult to explain which factors determine the higher activity of carcinomatous pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Obwohl diese Tumoren nicht in demselben Umfang analysiert wurden wie die zuvor genannten Entitäten, ist weitgehend klar, dass auf molekularer Ebene viele Gemeinsamkeiten mit dem HGSC bestehen [18]. Die epitheliale Komponente besitzt meistens Charakteristika eines HGSC, zudem wurde eine Assoziation mit einem serösen intraepithelialen Tubenkarzinom beschrieben [4].…”
Section: Karzinosarkom ("Maligner Müller-mischtumor")unclassified